Experimental study on the behavior of precast segmental column with domed shear key and unbonded Post-Tensioning tendon under impact loading - Zhang, Xihong; Hao, Hong; Li, C.; Do, T. (Pergamon, 2018)
Precast segmental columns have been more and more popularly used in constructions of prefabricated reinforced concrete (RC) structures in recent years. During its servicing life the precast segmental column might be subjected to lateral impact loads from hazards such as falling rock and vehicle collision etc., which however has not been well understood. It is therefore necessary to properly understand the response and vulnerability of segmental column under impact loading. A previous experimental study revealed that the trapezoidal prism shear key on concrete segment could effectively reduce lateral slippage between segments under lateral impact loading, but stress concentration near the shear key led to crushing damage to concrete segment. A new shear key design, i.e., domed shear key with smoothed curvature is proposed in this study. Precast segmental columns with domed shear key are fabricated and tested. This paper presents the test results of scaled segmental columns with this new shear key design. The performance of segmental column with the new dome shear key is compared with previously tested columns with trapezoidal shear key and plain segmental column without shear key. Furthermore, the segmental columns with the new domed shear keys were impacted at different locations along the column including the column mid-span, the segmental joint, and the bottom segment to examine the influences of different impact locations on their impact resistant capacities, and the response and failure modes.